Children’s programmes on nigerian television stations: a case of media neglect - Omotosho, Yewande; Oyero, Olusola; Salawu, Abiodun (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
This paper discusses the performance of Nigerian television stations as regards their programmes for children against the backdrop of responsibilities assigned to the media as partners in protecting the interest and rights of the child contained in various international conventions and treaties. The African Charter on Children's Broadcasting (ACCB) particularly stipulates regular, quality and diverse programming for children towards their physical, social and mental development. This study therefore analysed the content of three Nigerian television organisations to see how they have fared in this responsibility. The findings show a neglect of children on Nigerian television as only 3.3% of their total 818 programmes and 2.6% of the total airtime were devoted to children. However, most of the children’s programmes (70.4%) were produced locally and there was a balance in the focus of the programmes between entertainment and learning. Ironically, none of the television stations has a policy concerning children’s programming. We, therefore, recommend a holistic transformation in the Nigerian television stations’ programming for children. This will include regulatory framework for performance, giving more emphases to African Charter on Children's Broadcasting and other resolutions among broadcasters, and establishment of Kiddies’` televisions supported by the government.